1992
DOI: 10.1115/1.2920936
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinth Seal Rotordynamic Forces Using a Three-Dimensional Navier-Stokes Code

Abstract: A finite difference method for determining rotordynamic forces on an eccentric whirling labyrinth cavity has been developed. A coordinate-transformation was applied to the Reynolds time-averaged Navier-Stokes equations in order to use the modified bipolar coordinate system. The SIMPLER algorithm with QUICK differencing and the high Reynolds number k–ε turbulence model are used to compute the complex turbulent flowfield. A circular whirl orbit about the geometric center of the housing was specified for simplici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Currently, the CFD analysis for the rotordynamic characteristics of the labyrinth seal have been carried out by many authors including Rhode [13], Ishii [14], Moore [15], and Hirano [16]. Benefiting from the axisymmetric shape and the frequency-independent rotordynamic coefficients of the labyrinth seal, these authors employed a coordinate transformation to transform unsteady problem into a steady one by solving the three dimensional, eccentric flow fields in the frame of reference attached to the whirling rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the CFD analysis for the rotordynamic characteristics of the labyrinth seal have been carried out by many authors including Rhode [13], Ishii [14], Moore [15], and Hirano [16]. Benefiting from the axisymmetric shape and the frequency-independent rotordynamic coefficients of the labyrinth seal, these authors employed a coordinate transformation to transform unsteady problem into a steady one by solving the three dimensional, eccentric flow fields in the frame of reference attached to the whirling rotor.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer technology, computational fluid dynamics (CFD) has become an important method to predict the flow and forces in seals since the 1990s. Rhode et al [13,14] developed a three-dimensional finite difference approach and studied the influence of inlet swirl on the flow though a labyrinth seal. It was shown that the inlet swirl has a significant influence on the forces produced by the flow in seal.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the progress of computer technologies makes it possible to utilize a CFD program for predicting the rotordynamic force of rotating machinery seals. Rhode [7,8], Ishii [9] and Kwanka [10] calculated the rotordynamic force of gas labyrinth seals using the CFD programs they developed. Moore [11] used SCISEAL, a CFD code specially developed for the analysis of the seals, and compared the results with experiment results and the bulk flow programs.…”
Section: Introductionmentioning
confidence: 99%